Resilient and sustainable cities research, policy and practice - Allam, Zaheer; Chabaud, Didier; Gall, Catherine; Pratlong, Florent; Moreno, Carlos, 1959- (Elsevier, 2022)
The role of Cities in driving global economies has been well covered, and their impact on the larger ecosystem is well documented. Resilient and Sustainable Cities: Research, Policy and Practice explores how cities can be transformed into sustainable fabrics, while leading to positive socio-economic change. The topics include urban policy and covers the challenges cities experienced during the pandemic and resulting urban responses from federal, state, and local levels. This includes a transdisciplinary perspective dwelling on the city narrative, including Resources, Economics, Politics, and others. Resilient and Sustainable Cities serves as a valuable resource for leaders and practitioners working in Urban Policy and academia, as well as students in urban planning, architecture, and policy undergraduate and graduate level programs.